Mengembangkan Kognitif Anak Usia 4-5 Tahun dengan Permainan Gerbong Angka - Ahmad Fachrurrazi; Rizka Dwi Kurniawati (PT. Penerbit Tiga Mutiara, 2023)
Number carriage game which is a simple math learning activity that is easy to play and can solve or find the sum of the results provided by the educator. The purpose of this study is to describe the results of cognitive development in totaling to group A PAUD KIA-KIRA Sedati Sidoarjo. The data analysis technique uses 3 stages, namely data reduction; data presentation; and conclusions or verification. Then triagulation and validity are carried out. The group studied was Group A (ages 4-5 years) totaling 14 students. Data was collected from the results of observation sheets and field notes.The results showed that the cognitive development of group A PAUD KIA-KIRA in adding up with the numbers carriage game at the stage of development as expected (BSH) but on the indicator symbol of numbers at the stage began to develop (MB). Factors that support the implementation of the number car play activities, namely students who are enthusiastic to play even though there are some who are not familiar with numbers and homeroom teacher support is always helpful while the inhibiting factor is the cognitive ability to read the symbols of student numbers is still lacking, because the media at school is lacking inadequate as well as the lack of creativities educator makes educational props tools (APE).